The Effectiveness of Moringa Oleifera Leaf Extract on Hepatotoxic Case Reviewing from Cadmium, SGOT and SGPT Blood Levels in white Rats (Rattus norvegicus) Induced with Cadmium (Cd) - Devi Puspitasari; Indah Lestari; Christ Kartika Rahayuningsih; Juliana Christyaningsih (Jurnal Teknokes, 2022)
Moringa leaf (Moringa oleifera Lamk.) is part of herbal plants that have been known for their good natural chelating agent and hepatoprotective properties, especially in hepatotoxic events due to cadmium (Cd) exposure, where flavonoid compounds are contained in the form of quercetin and kaempferol, vitamin A, vitamin C and several phenol components that can inhibit the accumulation of cadmium metals and neutralize free radicals by lowering SGOT and SGPT levels, so this study aimed to determine the effectiveness of moringa leaf extract (Moringa oleifera Lamk.) against hepatotoxic in white rats (Rattus norvegicus) induced with cadmium. This study was expected to provide potential of Moringa leaves in hepatotoxic case at dose 400 mg/kgwb, 500 mg/kgwb and 600 mg/kgwb in white rats. This research was an experimental study with quantitative analysis conducted at the Faculty of Veterinary Medicine, Airlangga University, Surabaya Health Laboratory Center, and Bakti Analisa Laboratory in November 2021 – July 2022. The independent variable was the dose of Moringa leaf extract and the dependent variables were levels of cadmium, SGOT and SGPT in white rat blood. Analysis of blood cadmium levels using an atomic absorption spectrophotometer and analysis of SGOT SGPT levels using the BS-200 Chemistry Analyzer. The results showed that the average blood cadmium, SGOT and SGPT levels in treatment group 1 were 0.0605 μg/dL, 260.175 U/L, and 143.85 U/L; in treatment group 2 were 0.075 μg/dL, 250.925 U/L and 77.575 U/L; in treatment group 3 were 0.08125 μg/dL, 171.475 U/L and 66.075 U/L. Based on statistical analysis of One-way Anova test, sig. p value > 0.05, there was no significant difference in cadmium and SGOT levels. Then, the results of the Kruskal wallis test on SGPT levels showed sig. p value > 0.05, there was no significant difference in all treatments. Moringa leaf extract at a dose of 600 mg/kgbw/day had the best effect as chelating agent and hepatoprotective compared to doses of 400 mg/kgbw/day and 500 mg/kgbw/day at cadmium induction for 10 days. From this study, we recommend to consume about 66,522 g/day Moringa fresh leaves as the natural chelating agent and hepatoprotector for overcoming acute hepatotoxic case. INDEX TERMS Moringa Leaves, Cadmium, SGOT, SGPT, Rattus norvegicus, Atomic Absorption Spectrophotometer, Chemistry Analyzer